Severity of anaemia is associated with bone marrow haemozoin in children exposed to Plasmodium falciparum. (6th January 2014) - Aguilar, Ruth; Moraleda, Cinta; Achtman, Ariel H.; Mayor, Alfredo; Quintó, Llorenç; Cisteró, Pau; Nhabomba, Augusto; Macete, Eusebio; Schofield, Louis; Alonso, Pedro L.; Menéndez, Clara
Summary There are no large‐scale ex vivo studies addressing the contribution of Plasmodium falciparum in the bone marrow to anaemia. The presence of malaria parasites and haemozoin were studied in bone marrows from 290 anaemic children attending a rural hospital in Mozambique. Peripheral blood infections were determined by microscopy and polymerase chain reactions. Bone marrow parasitaemia, haemozoin and dyserythropoiesis were microscopically assessed. Forty‐two percent (123/290) of children had parasites in the bone marrow and 49% (111/226) had haemozoin, overlapping with parasitaemia in 83% (92/111) of cases. Sexual and mature asexual parasites were highly prevalent (62% gametocytes, 71% trophozoites, 23% schizonts) suggesting their sequestration in this tissue. Sixteen percent (19/120) of children without peripheral infection had haemozoin in the bone marrow. Haemozoin in the bone marrow was independently associated with decreased Hb concentration (P = 0·005) and was more common in dyserythropoietic bone marrows (P = 0·010). The results of this ex vivo study suggest that haemozoin in the bone marrow has a role in the pathogenesis of malarial‐anaemia through ineffective erythropoiesis. This finding may have clinical implications for the development of drugs targeted to prevent and treat malarial‐anaemia.